Review on narrow phase collision detection system in virtual environment - Sulaiman, Hamzah Asyrani; Othman, Azlishah Bin; Abd Aziz, Mohamad Zoinol Abidin; Bade, Abdullah (Asian Research Publishing Network (ARPN), 2015)
Collision detection is one of the most important tools that has been used widely in animation and simulation especially in computer games and medical simulation purpose. One of the critical issues in collision detection system is to actually prepared what kind of technique that is suitable for virtual environment to adapt collision detection system installed. Hence, this research